138k views
2 votes
Simplify for x. (10-5 2/3)×(-2)+x=8 2/3​

User Attmik
by
5.3k points

2 Answers

1 vote

Answer:

52/3

Explanation:

Rewrite this in improper fractions:

(10 - 17/3)(-2) + x = 26/3

Simplifying the quantity inside parentheses:

(30/3 - 17/3)(-2) + x = 26/3

Multiply both sides by 3 to eliminate the fractions:

(13)(-2) +3x = 26

Then, +3x = 26 + 26 = 52

Finally, 3x = 52 becomes x = 52/3

User Vishaal
by
5.2k points
3 votes

Answer:

16/37 I just did this... answer mines pls

Explanation:

User Krishh
by
5.4k points